Late Maastrichtian-early Paleocene iron (Fe) intensity data from ODP Site 208-1262, South Atlantic - James S K Barnet; Kate Littler; Dick Kroon; Melanie J Leng; Thomas Westerhold; Ursula Röhl; James C Zachos (PANGAEA, 2025)
Iron (Fe) intensity records measured by X-Ray Fluorescence (XRF) from ODP Site 1262 (Walvis Ridge, South Atlantic) covering the late Maastrichtian to early Paleocene (65.6 to 67.1 Ma). These data were measured between 2004 and 2007 and compiled to assess the magnitude of calcium carbonate dissolution at ODP Site 1262 during the Late Maastrichtian warming event and K/Pg boundary interval, since Fe is a proxy for clay content in the sediment.